The Value of Serum Tumor Markers and Blood Inflammation Markers in Differentiating Pancreatic Serous Cystic Neoplasms and Pancreatic Mucinous Cystic Neoplasms - Wang, Huan; Chen, Sihai; Shu, Xu; Liu, Zhijian; Liu, Pi; Zhu, Yong; Zhu, Yin; Xiong, Huifang (Frontiers in Oncology, 2022)
Although many studies have emphasized the prognostic and diagnostic value of tumor markers and various inflammation related markers, its clinical significance in differentiating benign and malignant pancreatic cystic neoplasms (PCN) remains to be clarified. This study explored the value of serum tumor markers and inflammation related biomarkers in the differentiation of pancreatic serous cystic neoplasms (SCN) and pancreatic mucinous cystic neoplasms (MCN). A total of 79 patients with PCN were included in this study, including 39 patients with SCN and 44 patients with MCN. Comparison of baseline data with preoperative results of serum tumor markers and associated inflammatory markers revealed significant differences in carbohydrate antigen 199 (CA199) and “lymphocyte×ALB” (LA) between the two groups (P=0.0023, P=0.0149, respectively). Univariate regression analysis showed that the increase of CA199 (OR=1.0034, P=0.0256) and the decrease of LA (OR=0.9752, P=0.0205) were the relevant risk factors of MCN. Finally, the receiver operating characteristic (ROC) curve was drawn and the area under ROC (AUC) was calculated to evaluate the prediction efficiency of each indicator. The results showed that CA199 and LA have good differential diagnostic efficacy for SCN and MCN, and LA was reported for the first time for the differential diagnosis of SNC and MCN.